Heterosis dan Daya Gabung Karakter Agronomi Cabai (Capsicum annuum L.) Hasil Persilangan Half Diallel - Ady Daryanto; Sriani Sujiprihati; Muhamad Syukur (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2010)
<!-- /* Font Definitions */ @font-face {font-family:Calibri; panose-1:2 15 5 2 2 2 4 3 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:-1610611985 1073750139 0 0 159 0;} /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-parent:""; margin-top:0cm; margin-right:0cm; margin-bottom:10.0pt; margin-left:0cm; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:Calibri; mso-fareast-font-family:"Times New Roman"; mso-bidi-font-family:"Times New Roman"; mso-ansi-language:IN; mso-no-proof:yes;} @page Section1 {size:612.0pt 792.0pt; margin:72.0pt 90.0pt 72.0pt 90.0pt; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0;} div.Section1 {page:Section1;} --> The objective of this research was to study heterosis and heterobeltiosis effects of ﬁ fteen chili genotypes (Capsicum annuum L.), the general combining ability (GCA) and speciﬁ c combining ability (SCA) of six chili inbred lines through half diallel crosses. The experiment was conducted from November 2008 to June 2009 using a Randomized Complete Block Design with three replications at IPB experimental ﬁ eld, Leuwikopo, Darmaga. Heterosis values were predicted based on the average values of their parents whereas heterobeltiosis were predicted based on the average values of the highest parents. Analyses GCA and SCA were based on the Grifﬁ ng’s ﬁ xed model of diallel design method II. Genotype IPB C2 had the highest GCA for fruit weight and fruit length. Genotype IPB C15 had the highest GCA for yield per plant and percentage of marketable fruit. Hybrid IPB C2 x IPB C14 and IPB C9 x IPB C14 had the highest heterosis, heterobeltiosis, and SCA for all fruit characters and yield per plant. Keywords: chili, hybrid, heterobeltiosis, yield.